Academic Performance of APEL Students in Open and Distance Learning - Norfardilawati Musa; Christina Mary Richard; Harvinder Kaur Dharam Singh; Cik Norazlina Mohamad; Rosinah Mahmood (ASEAN Journal of Open and Distance Learning, 2022)
Accreditation of Prior Experiential Learning (APEL) has paved greater access to lifelong learning opportunities. The systematic process of assessing prior learning for gaining access to higher education and accreditations for courses is a game-changing movement in Malaysian Education. Ministry of Higher Education (MOHE) introduced the Open Entry Admission System in 2006 and gave the mandate to the Open University Malaysia to be the pioneer for operationalising it nationwide. The main objective of introducing APEL in Malaysia is to democratise education and develop human capital. The enrolment of students entering open and distance learning (ODL) institutions through the APEL system has increased over the years. More universities have been appointed to be the assessment centres. However, there is a lack of studies investigating the performance of students who have undergone the APEL system for admission. Thus, this study aims to examine the academic performance of APEL students and how their demographic factors influence academic performance. A quantitative research approach will be employed to collect data on students’ academic performance based on the CGPA and demographic information. The population of this study was all learners under the Faculty of Business and Management (FBM). The results showed demographic factors such as age, marital status and type of programme does influence the APEL entrants’ academic performance (CGPA) This is significant findings as ODL institutions will be able to take necessary proactive measures to establish appropriate action for curbing dropout rates. (Abstract by authors)